Original paperThe impact of a vaginal brachytherapy boost to pelvic radiation in stage III endometrial cancer - Huddleston, Adam; Zhen, Sally; Qi, Lihong; Rash, Dominique; Leiserowitz, Gary; Mayadev, Jyoti (Journal of Contemporary Brachytherapy, 2015)
Purpose : We investigate the use and impact of a vaginal brachytherapy boost (VBB) after pelvic radiotherapy for stage III endometrial adenocarcinoma on vaginal and pelvic control. Material and methods : One hundred patients treated from 1998-2011 with surgery and adjuvant therapy with or without a VBB were included. Variables examined were grade, stage, lymphovascular space invasion (LVSI), vaginal involvement (VI), cervical stromal involvement (CSI), myometrial invasion (MI), and a VBB. Failure was scored as vaginal, or pelvic. Fisher’s exact test assessed association between variables with vaginal and pelvic control. Results: With a median follow up of 43 months, 31% were stage IIIA, 6% stage IIIB, and 63% stage IIIC. Thirty-eight (38%) received pelvic radiotherapy alone, and 62% received adjuvant chemotherapy. Of the 100 patients, 82 were treated with a VBB, 10 were not treated with a VBB, and 8 were not treated with RT. Of the 82 patients who received a VBB, 5 failed in the vagina with vaginal and pelvic control rates of 94% and 92%. The impact of VB reached borderline significance with its impact on pelvic control, 92% vs. 70% (p = 0.056), and did not affect vaginal control, 94% and 90% (p = 0.50). Neither tumor grade, LVSI, CSI, stage, nor LVSI (p > 0.05) statistically significantly impacted vaginal control. Conclusions : There are no clinical guidelines for the use of a VBB in stage III endometrial cancer. The majority of our patients were treated with a VBB and experienced excellent pelvic and vaginal control. The presence of traditional adverse features did not negatively impact control in our patient cohort. However, the role of a VBB needs further investigation to understand the incremental benefit beyond pelvic RT.